2001
DOI: 10.1074/jbc.m007103200
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Glutamate Decarboxylase Homologue Is Required for Normal Oxidative Stress Tolerance in Saccharomyces cerevisiae

Abstract: The action of ␥-aminobutyrate (GABA) as an intercellular signaling molecule has been intensively studied, but the role of this amino acid metabolite in intracellular metabolism is poorly understood. In this work, we identify a Saccharomyces cerevisiae homologue of the GABA-producing enzyme glutamate decarboxylase (GAD) that is required for normal oxidative stress tolerance. A high copy number plasmid bearing the glutamate decarboxylase gene (GAD1) increases resistance to two different oxidants, H 2 O 2 and dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
161
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(169 citation statements)
references
References 47 publications
7
161
0
1
Order By: Relevance
“…Two proteins are putative stress proteins, like the heat shock protein AN10202 (homologous to Ssa1p in yeast), or the GABA transaminase (AN2248), which homologous protein in yeast is involved in oxidative stress response (Coleman et al, 2001). We identified histone-2B as the only histone which could be an interaction partner of SasA.…”
Section: Protein Interaction Studies Revealed Involvement Of Sasa In mentioning
confidence: 99%
“…Two proteins are putative stress proteins, like the heat shock protein AN10202 (homologous to Ssa1p in yeast), or the GABA transaminase (AN2248), which homologous protein in yeast is involved in oxidative stress response (Coleman et al, 2001). We identified histone-2B as the only histone which could be an interaction partner of SasA.…”
Section: Protein Interaction Studies Revealed Involvement Of Sasa In mentioning
confidence: 99%
“…Previous studies have demonstrated that S. cerevisiae mutants lacking UGA1, UGA2 and UGA3 are incapable of growth on minimal medium with GABA as the sole nitrogen source, but grow normally on minimal medium with ammonium sulphate as the sole nitrogen source (Ramos et al, 1985;Coleman et al, 2001). To test the extent of interchangeable function of AtGABA-T and ScGABA-TKG in the cytosol and mitochondria, Δuga1 mutant was transformed with plasmid constructs containing AtGABA-T, with and without the mitochondrial targeting peptide or containing ScGABA-TKG or ScGABA-TKG with the mitochondrial targeting peptide.…”
Section: Gaba Transaminasesmentioning
confidence: 99%
“…NADPH can also be synthesized via succinate semialdehyde dehydrogenase encoded by the CESR gene SPAC139.05. A role for this enzyme in the response to stress has been suggested in S. cerevisiae (Coleman et al, 2001). Other CESR genes encode antioxidants such as catalase (cta1), glutathione peroxidase (gpx1), thioredoxin (trx2), glutaredoxin (grx1), glutathione-Stransferase (SPAC688.04), and metallothioneine (zym1), predicted protease genes (SPCC4G3.03, SPCC338.12, and isp6) as well as a gene involved in ubiquitination (SPAC2C4.15c) and gpd1 (encoding glycerol-3-phosphate dehydrogenase).…”
Section: Global Stress Responses In Fission Yeastmentioning
confidence: 99%